Perancangan Digital Library Management System Berbasis Web Menggunakan Metode SDLC pada SMAN 8 Muaro Jambi - Cindy Ermawati; Noneng Marthiawati; Hafiz Nugraha; Kevin Kurniawansyah (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
The rapid development of information technology has encouraged educational institutions to improve service quality through the implementation of information systems, including school library management. The library of SMAN 8 Muaro Jambi still faces several challenges in managing book data, member data, borrowing and returning transactions, and report generation, which are not yet fully integrated and reduce service efficiency. This study aims to design a web-based Digital Library Management System to improve the effectiveness and efficiency of library management. The research employed the System Development Life Cycle (SDLC) method, which consists of the planning, analysis, design, implementation, testing, and maintenance phases. The result of this study is a web-based digital library system capable of managing book collections, member records, borrowing and returning transactions, book searches, and report generation in an integrated manner. Based on the testing results, all system functions operated according to user requirements. The implementation of this system provides easier library data management, faster access to information, reduced recording errors, and improved effectiveness and efficiency of library services at SMAN 8 Muaro Jambi.